Molecular Characterization and Clinical Relevance of N6-Methyladenosine Regulators in Metastatic Prostate Cancer - Liu, Qiwei; Li, Zhen; He, Lizhao; Li, Ke; Hu, Chen; Chen, Jialiang; Zhou, Fangjian; Wang, Jun; Li, Yonghong; Xiao, Hengjun (Frontiers in Oncology, 2022)
Prostate cancer is a leading malignancy in the male population globally. N6-methylation of adenosine (m6A) is the most prevalent mRNA modification and plays an essential role in various biological processes in vivo. However, the potential roles of m6A in metastatic prostate cancer are largely unknown. In this study, we evaluated and identified two m6A modification patterns based on 21 m6A regulators in four public metastatic prostate cancer datasets. Different modification patterns correlated with distinct molecular characteristics. According to m6A-associated genes, we constructed a prognostic model, called m6Ascore, to predict the outcomes of patients with metastatic prostate cancer. We found that high m6A score level was related to dismal prognosis and characterized by higher cell cycle, DNA repair and mismatch repair pathway score. In vitro experiments confirmed that upregulation of METTL14, an m6A writer, enhanced the invasion, metastasis, and sensitivity of prostate cancer cells to poly (ADP-ribose) polymerase inhibitor. Conversely, down-regulation of potential target genes of m6A had the opposite effect. Finally, we validated that a higher m6A score was associated with a worse prognosis and a higher Gleason score in The Cancer Genome Atlas Program (TCGA) cohort. This work illustrated the nonnegligible role of m6A modification in multiple biological processes of metastatic prostate cancer. Evaluating the m6A risk scores of individual tumours will guide more effective judgement of prognosis as well as treatments for metastatic prostate cancer in clinical practice.